Greater Incidence of Both Fatal and Nonfatal Strokes in Disadvantaged Areas: The Northeast Melbourne Stroke Incidence Study - Thrift, Amanda G.; Dewey, Helen M.; Sturm, Jonathan W.; Paul, Seana L.; Gilligan, Amanda K.; Srikanth, Velandai K.; Macdonell, Richard A.L.; McNeil, John J.; Macleod, Malcolm R.; Donnan, Geoffrey A. (Stroke (1970), 2006)
Background and Purpose— Greater stroke mortality has been reported among lower socioeconomic groups. We aimed to determine whether fatal, nonfatal, and overall stroke incidence varied by socioeconomic status. Methods— All suspected strokes occurring in 22 postcodes (population of 306 631) of Melbourne, Australia, during a 24-month period between 1997 and 1999 were found and assessed. Multiple overlapping sources were used to ascertain cases with standard clinical definitions for stroke. Socioeconomic disadvantage was assigned in 4 bands from least to greatest using an area-based measure developed by the Australian Bureau of Statistics. Results— Overall stroke incidence (number per 100 000 population per year), adjusted to the European population 45 to 84 years of age, increased with increasing socioeconomic disadvantage: 200 (95% CI, 173 to 228); 251 (95% CI, 220 to 282); 309 (95% CI, 274 to 343); and 366 (95% CI, 329 to 403; χ 2 for ranks; P <0.0001). Similar incidence patterns were observed for both fatal and nonfatal stroke. Nonfatal stroke contributed most to this incidence pattern: 146 (95% CI, 122 to 169); 181 (95% CI, 155 to 207); 223 (95% CI, 194 to 252); and 280 (95% CI, 247 to 313; χ 2 for ranks; P <0.0001). Conclusions— In this population-based study, both fatal and nonfatal stroke incidence increased with increasing socioeconomic disadvantage. The greater contributor to this incidence pattern was nonfatal stroke incidence. This may have implications for service provision to those least able to afford it. Area-based identification of those most disadvantaged may provide a simple and effective way of targeting regions for stroke prevention strategies.